2011
DOI: 10.1149/1.3548113
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Model of SiGe Selective Epitaxial Growth using RPCVD Technique

Abstract: Recently, selective epitaxial growth (SEG) of B-doped SiGe layers has been used in recessed source/drain (S/D) of pMOSFETs. The uniaxial induced strain enhances the carrier mobility in the channel. In this work, a detailed model for SEG of SiGe has been developed to predict the growth rate and Ge content of layers in dichlorosilane(DCS)-based epitaxy using a reduced-pressure CVD reactor. The model considers each gas precursor contributions from the gas-phase and the surface. The gas flow and temperature distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 39 publications
(63 reference statements)
1
22
0
Order By: Relevance
“…12 However, for this process it has also been shown that some control of loading effects and pattern dependency can be achieved by adjusting the partial pressure of HCl. 13,14 A CVD deposition on blanket wafers may be described using the classical boundary layer theory. 15 In this theory, a laminar gas stream is flowing over the wafer.…”
Section: Resultsmentioning
confidence: 99%
“…12 However, for this process it has also been shown that some control of loading effects and pattern dependency can be achieved by adjusting the partial pressure of HCl. 13,14 A CVD deposition on blanket wafers may be described using the classical boundary layer theory. 15 In this theory, a laminar gas stream is flowing over the wafer.…”
Section: Resultsmentioning
confidence: 99%
“…The reason for pattern dependency relates to the gas kinetics and non-linear gas consumption over the patterned wafer [17,37,38]. The kinetics of CVD growth can physically be described by classical boundary layer theory assuming a laminar gas flow over the wafer [45].…”
Section: Pattern Dependency Of Segmentioning
confidence: 99%
“…The molecules are attracted towards the dangling bonds and are then consumed. The vertical diffusion path of the gas molecules was 10-15 mm for the total pressure of 20-40 torr in an Epsilon CVD reactor [37,39]. In the case of a chip with opening arrays, a virtual volume is established as shown in Fig.…”
Section: Pattern Dependency Of Segmentioning
confidence: 99%
See 2 more Smart Citations